A longitudinal study of residents' attitudes toward tourism development. Issue 23 (2nd December 2021) - Liang, Zengxian; Luo, Hui; Bao, Jigang
ABSTRACT: Deepening the understanding of residents' attitudes and related influencing factors is integral to tourism destinations' long-term sustainable development. Given the transitional nature of residents' attitudes, longitudinal research on the topic – despite having been recommended – remains lacking. This study applied a longitudinal design over a 4-year period to assess the effects of residents' satisfaction with tourism development and quality of life (QOL) on their attitudes toward tourism development. The study used a sample of tourism communities within China's Yuntai Mountain area, a mature and stable destination with a relatively independent and closed economic system. Results reflected a significant and positive impact of residents' satisfaction with tourism development on their attitudes toward such development; however, the mediating effect of QOL between residents' satisfaction and their attitudes was weak and not significant throughout the study period. These findings enrich the literature by re-examining residents' attitudes and associated influencing factors over time. Targeted strategies are recommended to help local governors and policymakers engender greater resident support for tourism.